Suicide and political regime in New South Wales and Australia during the 20th century. Issue 10 (1st October 2002) - Page, A; Morrell, S; Taylor, R
Abstract : Study objective: Australia has had a two party parliamentary political system for most of the period since its Federation in 1901, dominated either by a social democratic (Labor) or a conservative ideological perspective. This paper investigates whether such political differences at Federal and State levels have influenced suicide rates in the state of New South Wales (NSW) for the period 1901–1998. Design: Federal government type, NSW State government type, and combinations of both Federal and NSW State government type were examined. Poisson regression models were stratified by sex and controlled for the effects of age, annual change in gross domestic product, sedative availability, drought, and both world wars. Results: When both Federal and NSW State governments were conservative the relative risk of suicide for NSW men was 1.17 (p<0.001) and for women 1.40 (p<0.001) compared with both governments being Labor (1.00). A statistically significant linear trend (p<0.001) in suicide risk was evident across the continuum of Federal/State government combinations, from both Labor (lowest), to mixed (intermediate), to both conservative (highest). Conclusion: Significantly higher suicide risk was associated with conservative government tenures compared with social democratic incumbents. Results are discussed in terms of the differences underpinning conservative and social democratic government programme ideology, and their relevance to Durkheim's theories of suicide, social regulation, and integration.